Do campo da pesquisa ao campus do conhecimento: Instrumentalização da literacia de informação em meio académico - Sanches, Tatiana (2012)
This study seeks to explain how information literacy can contribute effectively to the construction and production of knowledge in academic context, ie, as from this domain and its instrumentalization is possible to prepare the time when the college student feels able to produce and record new knowledge through writing. Based on the ideas of emancipation and empowerment of the third cycle student's, principles guaranteed by the university pedagogy, it is proposed that the university library can contribute with training in information literacy, not only for research, evaluation and selection of information, but also for the production and presentation of scientific knowledge by the university student, ambition and goal of higher education.